1999
DOI: 10.1093/nar/27.20.4050
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase III is essential for accurate nuclear division in Schizosaccharomyces pombe

Abstract: Topoisomerases catalyse changes in the topological state of DNA and are required for many aspects of DNA metabolism. While the functions of topoisomerases I and II in eukaryotes are well established, the role of topoisomerase III remains poorly defined. We have identified a gene in the fission yeast Schizosaccharomyces pombe, designated top3 (+), which shows significant sequence similarity to genes encoding topoisomerase III enzymes in other eukaryotic species. In common with murine TOP3 alpha, but in contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
95
0
1

Year Published

2001
2001
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 18 publications
6
95
0
1
Order By: Relevance
“…cellular role of the type IA DNA topoisomerases. Furthermore, any postulate invoking a critical role of a type IA DNA topoisomerase in the resolution of newly replicated chromosome pairs cannot explain the observation that the defects owing to inactivation of these enzymes can be suppressed by mutations in homologous recombination genes (4,(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…cellular role of the type IA DNA topoisomerases. Furthermore, any postulate invoking a critical role of a type IA DNA topoisomerase in the resolution of newly replicated chromosome pairs cannot explain the observation that the defects owing to inactivation of these enzymes can be suppressed by mutations in homologous recombination genes (4,(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…Concordantly, inactivation of the E. coli recA gene, which is essential for homologous recombination, restores viability of a topA topB double mutant lacking both DNA topoisomerases I and III (4). Earlier studies also showed that the defects of mitotic yeast top3 cells could largely be suppressed by mutations in a helicase of the RecQ family, the Sgs1 protein in S. cerevisiae and the Rqh1 protein in Schizosaccharomyces pombe (6,8,9). Extensive studies of physical and functional interactions between the type IA DNA topoisomerases and RecQ helicases have been carried out (6,(9)(10)(11)(12)(13)(14)(15), prompted by the identification of the human Bloom and Werner syndrome proteins as RecQ helicases (16,17).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…On the basis of studies in Escherichia coli and the yeasts Saccharomyces cerevisiae and Schizosaccharomyces pombe, the type IA DNA topoisomerases are most likely involved in chromosome segregation, especially in the resolution of chromosomes that had undergone recombinational repair (4,(44)(45)(46)(47)(48). In animals, the possibility of recombinational repair of mtDNA remains uncertain (reviewed in ref.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in yeast and mammalian cells have provided strong evidence for physical and functional interaction between type IA DNA topoisomerases and helicases of the RecQ family (45)(46)(47)(54)(55)(56)(57)(58). In mammalian cells, Top3␣ has been suggested to interact with the BLM helicase.…”
Section: Discussionmentioning
confidence: 99%